Determination of the Concentration of Tm3+ and Ho3+ Ions in the Glass and Crystalline Phases in Oxyfluoride Glass Ceramics by Absorption Spectra Analysis - A. S. Yasukevich; V. E. Kisel; E. E. Trusova; G. E. Rachkovskaya; G. B. Zakharevich; K. B. Podbolotov; V. S. Gurin (Приборы и методы измерений)
Optical glass ceramics based on oxyfluoride glasses activated by rare earth ions have attractive properties for development of lasers and near-infrared amplifiers, since they combine properties of fluoride crystals with low phonon frequencies and chemical and mechanical properties of oxide matrices. Spectroscopic properties of activator ions in crystalline and glass phases of glass-ceramics can differ significantly. Thus, it is possible to determine impurity ions’ distribution between these phases by means of absorption or luminescence spectra analysis. The main goal of this work was to develop a method for determining the concentration of Tm3+ and Ho3+ ions in the crystalline, PbF2 and glassy phases of glass ceramics after secondary thermal treatment of thulium-doped and thulium-holmium co-doped oxyfluoride glasses. Spectroscopic characteristics of oxyfluoride glasses activated by Tm3+ ions and co-activated by Tm3+ and Ho3+ ions, as well as glass ceramics obtained from the original glasses as a result of secondary heat treatment were studied. It was established by X-ray phase analysis method that under certain heat treatment conditions crystalline β-PbF2 phase is formed in those glasses. Absorption and luminescence spectra of Tm3+ and Ho3+ impurity ions in the original glass and in β-PbF2 crystals were compared with their ones in glass ceramics. A method for determining the concentration of ions in the crystalline and glass phases of glass ceramics was proposed on the basis of this comparison. Dependence of Tm3+ and Ho3+ ions distribution between the glass and crystalline phases on different regime of glasses' secondary heat treatment was studied.